Catalytic asymmetric conjugate arylation of γ,δ-unsaturated β-dicarbonyl compounds - Yao, Jian (2020)
The first catalytic asymmetric conjugate addition to γ,δ-unsaturated β-dicarbonyl compounds was developed. With a chiral diene-rhodium(I) μ-chloro dimer as the catalyst in toluene/H2O, asymmetric conjugate arylation of γ,δ-unsaturated β-dicarbonyl compounds with arylboronic acids proceeded in high efficiency with excellent enantioselectivities. The generated β-dicarbonyl products are versatile chiral synthons, which can be easily converted to diverse important chiral structures.